First report of brown widow spider sightings in Peninsular Malaysia and notes on its global distribution - Muslimin, M.; Wilson, J.J.; Ghazali, A.R.; Braima, K.A.; Jeffery, J.; Wan-Nor, F.; Alaa-Eldin, M.E.; Mohd-Zin, S.W.; Wan-Yusoff, W.S.; Norma-Rashid, Y.; Lau, Y.L.; Rohela, M.; et al. (BMC, 2015)
Background: The brown widow spider (Latrodectus geometricus Koch, 1841) has colonised many parts of the world from its continent of origin, Africa. By at least 1841, the species had successfully established populations in South America and has more recently expanded its range to the southern states of North America. This highly adaptable spider has been far more successful in finding its niche around the world than its famous cousins, the black widow, Latrodectus mactans, found in the south-eastern states of North America, and the red-back, Latrodectus hasselti, found mostly in Australia, New Zealand and Japan. Methods: We performed an extensive web search of brown widow sightings and mapped the location of each sighting using ArcGIS. Specimens reputedly of the species L. geometricus were collected at three localities in Peninsular Malaysia. The spiders were identified and documented based on an examination of morphological characteristics and DNA barcoding. Results: The spiders found in Peninsular Malaysia were confirmed to be Latrodectus geometricus based on their morphological characteristics and DNA barcodes. We recorded 354 sightings of the brown widow in 58 countries, including Peninsular Malaysia. Conclusion: Reports from the Americas and the Far East suggest a global-wide invasion of the brown widow spider. Herein we report the arrival of the brown widow spider in Peninsular Malaysia and provide notes on the identification of the species and its recently expanded range.